To complete the table for the function \( y = x^3 - 4 \), we will substitute each value of \( x \) into the equation and solve for \( y \).
-
For \( x = -3 \): \[ y = (-3)^3 - 4 = -27 - 4 = -31 \]
-
For \( x = -2 \): \[ y = (-2)^3 - 4 = -8 - 4 = -12 \]
-
For \( x = -1 \): \[ y = (-1)^3 - 4 = -1 - 4 = -5 \]
-
For \( x = 0 \): \[ y = (0)^3 - 4 = 0 - 4 = -4 \]
-
For \( x = 1 \): \[ y = (1)^3 - 4 = 1 - 4 = -3 \]
-
For \( x = 2 \): \[ y = (2)^3 - 4 = 8 - 4 = 4 \]
-
For \( x = 3 \): \[ y = (3)^3 - 4 = 27 - 4 = 23 \]
Now, we can summarize the completed table:
| \( x \) | \( y \) | |:---------:|:---------:| | -3 | -31 | | -2 | -12 | | -1 | -5 | | 0 | -4 | | 1 | -3 | | 2 | 4 | | 3 | 23 |
Feel free to ask if you need any further assistance!